Analyzing the Synchronization between the Financial and Business Cycles in Turkey - Akar, Cüneyt (Journal of Reviews on Global Economics, 2016)
The primary purpose of this study was to investigate the relationships between the financial and business cycles in Turkey. A quarterly dataset was used for the analysis that covers the period from 1998Q1 to 2014Q4. The cycles were obtained with a Hodrick-Prescott (HP) filter design. The concordance index values, cross-correlation values and Dynamic Conditional Correlation (DCC) model were used to identify the characteristics of the relationships between the financial and business cycles. The empirical results revealed that the financial and business cycles are highly synchronized in Turkey. The results also indicate that while the credit volume cycle is the leading factor of the GDP cycle, the GDP cycle leads from the BIST 100 cycle in Turkey. The last significant conclusion is that the positive and high dynamic conditional correlations between the financial and business cycles experienced a break during the 2008 global crisis.